New pieces in the transmission cycle of the hepatitis E virus in South America: first viral detection in wild boars from Argentina - Pisano, Belén M. (2019)
Fil: Pisano, Belén M. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Instituto de Virología‘Dr. J. M. Vanella’; Argentina